Prosthetic rehabilitation of a total laryngectomy patient - Pulkit Jain; Amit Siwach; Gurleen Arora; Richa Agarwal (Wolters Kluwer Medknow Publications, 2015)
The fundamental objective in restoring a defect created after total laryngectomy with a custom made silicone prosthesis is to enable the patient to cope better with the difficult process of rehabilitation after a major surgery has been performed. A cosmetically acceptable prosthesis that reproduces the color and form and allows the patient to return to his/her accustomed lifestyle. A sequence of steps for construction of custom-made laryngeal prosthesis is outlined in this case report using the readily available materials and method which any prosthodontist can readily understand and deliver.